Identifying Residents' Health Issues Six Weeks after the Great East Japan Earthquake. Issue 6 (28th May 2015) - Teramoto, Chie; Nagata, Satoko; Okamoto, Reiko; Suzuki, Ruriko; Kishi, Emiko; Nomura, Michie; Jojima, Noriko; Nishida, Masumi; Koide, Keiko; Kusano, Emiko; Iwamoto, Saori; Murashima, Sachiyo
Abstract Objective The aim of this study was to identify the characteristics and health issues of residents in need of assistance in a town affected by the Great East Japan Earthquake, six weeks after the disaster, through an outreach initiative. Design and Sample A cross‐sectional qualitative design was used. Public health nurses conducted comprehensive semi‐structured interviews during home visits with residents. A total of 5, 082 residents from the affected town. Measures These included demographic information, public records of the extent of the damages, and qualitative interview data to determine the urgency of the necessary interventions. Results A total of 281 residents needed some kind of assistance and were identified as "requiring early intervention (within two weeks)" or "requiring assistance (within 12 weeks)." The most common health issue requiring early intervention was "interruption of treatment" (25.0%), followed by "need for mental care." The most frequent health issue requiring assistance within 12 weeks was the "need for mental health care" (39.7%), followed by "interruption of treatment, " and "need for nursing care." Conclusions During a disaster, it is imperative to identify cases requiring early intervention. Home‐visit interviews were necessary to identify existing health concerns to prevent the development of more serious health problems.